2021
DOI: 10.1038/s41598-021-84015-0
|View full text |Cite|
|
Sign up to set email alerts
|

The effects of acarbose therapy on reductions of myocardial infarction and all-cause death in T2DM during 10-year multifactorial interventions (The Beijing Community Diabetes Study 24)

Abstract: To investigate the potential benefits of acarbose therapy on cardiovascular events (CVD) in Type 2 diabetes (T2DM) in an urban community over 10-year follow-up. The study population of Beijing Community Diabetes Study (BCDS) were type 2 diabetes (T2DM) living in 21 communities in Beijing. All patients received comprehensive intervention in accordance with the Chinese guidelines for the prevention and treatment of diabetes. Professors in endocrinology from top tier hospitals regularly visited the communities fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Acarbose also increases the median lifespan of male mice by 16-17% and that of female mice by 4-5% ( Harrison et al, 2019 ). In humans, acarbose therapy significantly reduced the incidence of myocardial infarctions and all-cause deaths in patients with type 2 diabetes, suggesting that acarbose can improve health and thus potentially extend lifespan ( Zhang et al, 2021 ). Currently, acarbose is in Phase 2 clinical trials to study its effects during ageing in individuals aged 60-100 years ( Garay, 2021 ).…”
Section: Ras/mapk Signalling In Ageing: Genetic Evidence From Model O...mentioning
confidence: 99%
“…Acarbose also increases the median lifespan of male mice by 16-17% and that of female mice by 4-5% ( Harrison et al, 2019 ). In humans, acarbose therapy significantly reduced the incidence of myocardial infarctions and all-cause deaths in patients with type 2 diabetes, suggesting that acarbose can improve health and thus potentially extend lifespan ( Zhang et al, 2021 ). Currently, acarbose is in Phase 2 clinical trials to study its effects during ageing in individuals aged 60-100 years ( Garay, 2021 ).…”
Section: Ras/mapk Signalling In Ageing: Genetic Evidence From Model O...mentioning
confidence: 99%
“…It has also been found that acarbose reduces cardiovascular events in patients with IGT and T2DM. In a recently published study, Zhang et al [ 11 ] found a 50% relative risk (RR) reduction in myocardial infarction and a 52% RR reduction in all-cause deaths after a 10-year follow-up with regard to acarbose therapy in patients with T2DM[ 11 ]. This effect is due to the reduction of oxidative stress caused by the lowering of postprandial two-hour blood sugar.…”
Section: Introductionmentioning
confidence: 99%